Текстовий концепт КОХАНКА в межах розгортання текстового мегаконцепту ЖІНОЧНІСТЬ у французьких соціально-побутових романах ХІХ–ХХ ст. - Буць, Ж. В.; Buts Zh. V., Zh. V. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
У статті розглянуто концептуальний простір французьких соціально-побутових романів ХІХ–ХХ ст. Особливу увагу приділено особливостям розгортання текстового концепту КОХАНКА в межах текстового мегаконцепту ЖІНОЧНІСТЬ у досліджуваному різновиді художньої романістики. This article carries out the analyse of the conceptual space of French social and life novels of the ХІХ–ХХ centuries. A particular attention is payed to the scan of the textual concept LOVER within the scope of the textual megaconcept FEMININITY in French social and life novels of the ХІХ–ХХ centuries.
The Textual Concept LOVER in Scan of the Textual Megaconcept FEMININITY in French Social and Life Novels of the ХІХ–ХХ Centuries
Keywords: текстовий концепт; французькі соціально-побутові романи; ЖІНОЧНІСТЬ; КОХАНКА; textual concept; French social novel; FEMININITY; LOVER